2004
DOI: 10.2134/agronj2004.0986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Swine Slurry on Alfalfa Production and on Tissue and Soil Nutrient Concentration

Abstract: surface water pollution are causing swine and dairy producers to reconsider their management strategies (Bo-Alfalfa (Medicago sativa L.) may not be the most suitable crop det et al., 2001; Soil and Water Conserv. Soc., 1998; to utilize all the manure nutrients, but it may be the best crop available, especially when the crop is dormant. The objective of this research was Dané s et al., 1995). to investigate the effect of swine (Sus scrofa domesticus) slurry manure In several alfalfa-producing areas, alfalfa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 13 publications
5
28
1
2
Order By: Relevance
“…However, in cropping systems where the shoot drymatter is removed from the soil surface, e.g., in the case of some species used in pastures, even with the addition of high amounts of K fertilizers, the concentrations of available K in soil may have a negative balance. This was observed by Lloveras et al (2004) in soils with alfalfa and treated with annual pig slurry applications (0, 25 and 50 m 3 ha -1 ) for two years. Similar results were reported by Ceretta et al (2003) in Paraíso do Sul, RS, where after 28 pig slurry applications in four years and removal of the pasture every time it was cut, even with manure application rates of up to 40 m 3 ha -1 , the available K content was lower than in the area without manuring.…”
Section: Table 3 Amounts Of Total and Mineral Nitrogen (N) In Layersmentioning
confidence: 63%
See 1 more Smart Citation
“…However, in cropping systems where the shoot drymatter is removed from the soil surface, e.g., in the case of some species used in pastures, even with the addition of high amounts of K fertilizers, the concentrations of available K in soil may have a negative balance. This was observed by Lloveras et al (2004) in soils with alfalfa and treated with annual pig slurry applications (0, 25 and 50 m 3 ha -1 ) for two years. Similar results were reported by Ceretta et al (2003) in Paraíso do Sul, RS, where after 28 pig slurry applications in four years and removal of the pasture every time it was cut, even with manure application rates of up to 40 m 3 ha -1 , the available K content was lower than in the area without manuring.…”
Section: Table 3 Amounts Of Total and Mineral Nitrogen (N) In Layersmentioning
confidence: 63%
“…These results show that there was K transfer by percolation and transfer of available K in runoff was also stated by Ceretta et al (2010). As the shoot dry matter of crops was not withdrawn, the hypothesis of Lloveras et al (2004) that there is great export of K through the shoot dry matter of crops could not be considered in this study. However, it was possible to maintain high levels of available K in the 0-10 cm layer with successive pig slurry applications, considered ideal by the CQFSRS/SC (2004).…”
Section: Table 3 Amounts Of Total and Mineral Nitrogen (N) In Layersmentioning
confidence: 77%
“…It is not necessary to fertilise with Cu for alfalfa (WERNER et al, 1997). Lloveras et al (2004) applied swine manure (25 and 50 m 3 ha -1 ) to alfalfa and found similar concentrations of Cu; however, there was no significant increase after manure treatment for poor soil after two years. Additionally, the concentrations of Fe were lower than this study, and showed a significant increase with a treatment of 50 m 3 ha -1 compared to the control soil fertility, which was slightly higher.…”
Section: Resultsmentioning
confidence: 92%
“…Treatments of 100 and 200 m 3 ha -1 were nearly at a 3:1 ratio. Lloveras et al (2004) If we compare the concentration of Ca and Mg in the soil at the beginning of the experiment (13:06 mmol dm -3 , respectively), we see that all treatments increased in concentration with the application of biofertiliser; however, the concentration was much higher for the 200 and 400 m 3 ha -1 treatments (Figure 2). …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation